Long-distance running routes' flat equivalent distances from race results and elevation profiles - Smet, D.; Verleysen, M.; Francaux, M.; Baijot, L. (Proceedings of the 6th International Conference on Sport Sciences Research and Technology Support - Volume 1: icSPORTS, 2018)
Running routes` elevation profiles affect their runnability and therefore athletes` average speeds: route distances alone are not sufficient to predict or evaluate running times. This is an issue for race preparation, race strategy, performance comparison and runner workload planning anytime the ground is sloping. This paper proposes a methodology to establish route equivalent distances expressed as a function of their elevation profiles. The same expression can be used to compute gradient adjusted speeds either for athlete pacing during races or to analyze their performances afterward. The approach is first based on race results and addresses the problem of attendees` level disparities by evaluating races and athletes at the same time using a race performance model. Subsequently, this paper use polynomial and piecewise linear regressions on the instant slope along the routes to express equivalent distances. They match previous studies with constant slopes and extend to the case of v arying slopes.